2023
DOI: 10.3389/fnagi.2023.1199612
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models of cerebral injury and cognitive impairment in hypertension

Abstract: Hypertension is a major risk factor for dementia, including both vascular and neurodegenerative etiologies. With the original aim of studying the effect of blood pressure elevation on canonical target organs of hypertension as the heart, the vasculature or the kidneys, several experimental models of hypertension have sprouted during the years. With the more recent interest of understanding the cerebral injury burden caused by hypertension, it is worth understanding how the main models of hypertension or locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“… 177 Available models can, however, be used to differentiate the effects of hypertension from atherosclerosis and investigate AD‐related processes (reviewed in Ref. 178 ) (Table 3 ). In C57Bl/6J (wild‐type) mice, hypertension due to transverse aortic constriction causes brain Aβ deposition, triggers proinflammatory cytokine production, and impairs cognition.…”
Section: Cardiometabolic Modifiable Risk Factorsmentioning
confidence: 99%
“… 177 Available models can, however, be used to differentiate the effects of hypertension from atherosclerosis and investigate AD‐related processes (reviewed in Ref. 178 ) (Table 3 ). In C57Bl/6J (wild‐type) mice, hypertension due to transverse aortic constriction causes brain Aβ deposition, triggers proinflammatory cytokine production, and impairs cognition.…”
Section: Cardiometabolic Modifiable Risk Factorsmentioning
confidence: 99%
“…Several animal models of hypertension allowed investigation of the effects of high blood pressure on the brain and provided valuable knowledge of the potential mechanisms underlying cerebrovascular damage. [12][13][14][15] However, monitoring the progressive development of lesions and respective locations in the mouse brain is still difficult, suggesting the need to implement adequate investigative tools. We and others have previously shown that transverse aortic constriction (TAC) is a relevant experimental model that mechanically increases blood pressure and progressively leads to cerebral injury and cognitive impairment.…”
mentioning
confidence: 99%